2010
DOI: 10.5251/abjna.2010.1.5.878.885
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between electrical conductivity, softening and color of Fuerte avocado fruits during ripening

Abstract: To identify the most important ripening parameters of Fuerte avocado fruits, and to quantify the relationship between color changes, electrical conductivity and softening of avocado fruits, the ripening process was investigated to fulfill the consumer and market demands. Mature and high quality avocado fruits (Persea Americana Mill.) were held to ripe at 20 o C in controlled temperature rooms with 90-95% relative humidity for two weeks. Fruit quality characteristics (respiration rate, soluble solids content (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
(25 reference statements)
5
13
0
Order By: Relevance
“…It was observed that the electrical conductivity of intact “Hass” avocado flesh increased significantly ( p < .05) as the fruit ripened (Figure ), indicating the breakdown of cell membranes in the avocado mesocarp as the fruit ripened. These results agree with the previous study of Montoya, De La Plaza, and Lopez‐Rodriguez () and Ahmed, Yousef, and Hassan () where electrical conductivity of the “Hass” and “Fuerte” avocado fruit tissue increased as the fruit softened due to ripening. The electrical conductivity of fruit pulp tissue increased significantly ( p < .05) after grinding, and the softer avocado fruit showed higher conductivity values at 0, 60, and 120 min of malaxing (Figure ), which confirms EIS results that cells in softer fruit are more likely to be disrupted releasing more ions into the apoplast.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It was observed that the electrical conductivity of intact “Hass” avocado flesh increased significantly ( p < .05) as the fruit ripened (Figure ), indicating the breakdown of cell membranes in the avocado mesocarp as the fruit ripened. These results agree with the previous study of Montoya, De La Plaza, and Lopez‐Rodriguez () and Ahmed, Yousef, and Hassan () where electrical conductivity of the “Hass” and “Fuerte” avocado fruit tissue increased as the fruit softened due to ripening. The electrical conductivity of fruit pulp tissue increased significantly ( p < .05) after grinding, and the softer avocado fruit showed higher conductivity values at 0, 60, and 120 min of malaxing (Figure ), which confirms EIS results that cells in softer fruit are more likely to be disrupted releasing more ions into the apoplast.…”
Section: Resultssupporting
confidence: 92%
“…Fv, firmometer value "Hass" avocado flesh increased significantly (p < .05) as the fruit ripened ( Figure 3), indicating the breakdown of cell membranes in the avocado mesocarp as the fruit ripened. These results agree with the previous study of Montoya, De La Plaza, and Lopez-Rodriguez (1994) and Ahmed, Yousef, and Hassan (2010) where electrical conductivity of the "Hass"…”
Section: Electrical Conductivitysupporting
confidence: 93%
“…The suppressed PG activities by CST ( Fig 5 ) were concurrent with the delayed fruit softening in both naturally ripened fruit and ethylene-treated fruit ( Fig 4 ), indicating that PG activity is one of the key modulating factors for fruit softening. Unlike PG activity, PME activity of avocado fruits tended to decrease throughout the shelf life, which was consistent with results of a previous study [ 31 ]. No significant difference in PME activity between control and cold shock-treated fruits was observed ( Fig 6 ).…”
Section: Resultssupporting
confidence: 92%
“…The measurements are quite stable. A dielectric contrast exists among the three states, with a nonmonotonic profile, consistent with the well-known physical/chemical variations described in the literature, which are nonmonotonic as well [27], [29], [30] (especially regarding the oil and sugar concentration). Table 1.…”
Section: Complex Permittivitysupporting
confidence: 86%